Neoplastic intestinal occlusion in the mediate postoperative period of prism laparoscopic cholecystectomy - Praderi, Raúl; Cilleruello, Roberto; Praderi, José; Navarrete, Héctor (Cirugía del Uruguay, 1997)
A male patient who had undergone laparoscopic cholecystectoiny was reoperated befare a month had passed far a jejunal occlusion due to invaginated carcinoma of the second ansa which had been resected in a first operation.